The concept and the main criteria of reputation capital - Temirbayeva, Ж.; Rystina, И. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article discusses the role of intangible assets in the formation of the company’s reputation capital. By conducting a comparative analysis of definitions, the author’s interpretation of the concept of “reputation capital» is proposed. In conclusion, it is concluded that reputation capital provides the company with competitive advantage in the business environment and serves as a source of increasing its market value. It is noted that the main component of reputation capital is reputation, which through investments in the quality of the product, corporative culture, social responsibility of the business is converted into the capital